Understanding the Continuation of Firm Activities when Entrepreneurs Exit their Firms: Using Theory of Planned Behavior. (25th October 2013) - Leroy, Hannes; Manigart, Sophie; Meuleman, Miguel; Collewaert, Veroniek
<x xml:space="preserve">Abstract</x> Up to now, little attention has been paid to the continuity of a firm when entrepreneurs exit. Survey data from 175 entrepreneurs confirm the theory of planned behavior as an appropriate framework to understand whether entrepreneurs, when leaving, sell or liquidate their firm. Entrepreneurs' sale attitudes are related to sale intentions, which are associated with firm sale. Further, sale attitudes are positively related to whether entrepreneurs perceive firm continuation to be out of free will, their experience, the number of employees, and whether the firm is a multigeneration family business.